Modeling and control of operator functional state in a unified framework of fuzzy inference petri nets - Zhang, Jian-Hua; Xia, Jia-Jun; Garibaldi, Jonathan M.; Groumpos, Petros P.; Wang, Ru-Bin (Elsevier, 2017)
Background and objective: In human-machine (HM) hybrid control systems, human operator and machine cooperate to achieve the control objectives. To enhance the overall HM system performance, the discrete manual control task-load by the operator must be dynamically allocated in accordance with continuous-time fluctuation of psychophysiological functional status of the operator, so-called operator functional state (OFS). The behavior of the HM system is hybrid in nature due to the co-existence of discrete task-load (control) variable and continuous operator performance (system output) variable.